FUNCTIONAL ASSESSMENT IN FAMILIES OF PEOPLE WITH SUICIDAL BEHAVIOR: APPLICATION OF THE CALGARY MODEL - Andrade, Isabela Carolyne Sena de; Gomes, Nadirlene Pereira; Correia, Cíntia Mesquita; Virgens, Ionara da Rocha; Santos, Josinete Gonçalves dos; Santos, Joana D’arc Ferreira Lopes; Telles, Sabrina de Oliveira Silva (Cogitare Enfermagem, 2024)
Objective: unveil the actions that maintain the functionality of the family of people with suicidal behavior. Method: this is a qualitative, descriptive-exploratory study, based on the theoretical and methodological framework of the Calgary Family Assessment Model. 11 users of the Suicide Study and Prevention Center, located in Salvador, Bahia, Brazil, participated in the online meeting in 2022 to construct the family genogram. In the second stage, the interview included nine user families. Results: the following categories emerged: surveillance by family members; family member’s use of technology for daily contact; management of the suicidal crisis by family members and family attention to basic needs, all categories related to a person with suicidal behavior. Conclusion: there are ways to implement health policies and manuals that guide family and friends in managing the suicidal crisis, thus avoiding undesirable consequences, such as the suicide attempt and the completed act.